Contesting Catholicity: Theology for Other Baptists. Five Perspectives - III - Contesting Catholicity: Theology for Other Baptists. By Curtis W. Freeman. Waco, TX: Baylor University Press, 2014. xi + 466 pages. $49.95. - Doyle, Dennis M. (Horizons, 2015)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0360966915001012/resource/name/firstPage-S0360966915001012a.jpg